Immigrant entrepreneurs in the USA: A conceptual discussion of the demands of immigration and entrepreneurial intentions - Yemisi Freda Awotoye; Robert P. Singh (New England Journal of Entrepreneurship (NEJE), 2018)
Purpose - Given the growing number of immigrant entrepreneurs in the USA, the purpose of this paper is to better understand the behaviors of this subgroup of entrepreneurs. Specifically, the paper aims to understand the unique challenges faced by immigrant entrepreneurs and how environmental challenges affect decisions to grow or abandon their ventures. Design/methodology/approach - To make the theoretical arguments in this conceptual paper, the authors draw on the theory of planned behavior developed by Ajzen (1985), which suggests that a person's behavior is predicted by their intention, and intentions are predicted by one's attitudes, subjective norm and perceived behavioral control. Findings - The paper provides theoretical insights on the effect of demands of immigration on the intentions of immigrant entrepreneurs to engage in three specific entrepreneurial behaviors: new venture formation, growth and abandonment. The authors propose that immigrant entrepreneurs deal with increased stress yet continue to maintain higher intentions to found new ventures compared to non-immigrants. Contrastingly, the authors also propose that the stress and obstacles immigrant entrepreneurs face reduce their intentions to grow their firms and increase their intentions to abandon their firms. The authors also explore entrepreneurial resilience as a possible moderating factor between stress and entrepreneurial intentions of immigrant entrepreneurs. Research limitations/implications - First, the authors do not distinguish between immigrants from different nations or parts of the world or having different backgrounds. Second, the authors do not fully develop or incorporate the element of coping. Also, our paper is limited to behaviors of immigrant entrepreneurs with micro- and small-businesses. Practical implications - Venture capitalists could benefit from empirical results of these propositions as funding decisions may need to include consideration of the proposed effects of stress and demands of immigration. Originality/value - This paper meets an identified need to examine the effects of immigrant-specific issues such as the demands of immigration on the behaviors of this growing group of entrepreneurs.
Keywords: 650; Stress; Resilience; Growth; Entrepreneurial intentions; Abandonment; Immigrant entrepreneur